Investigation on Thrombocytopenic Events of Linezolid at Dong Nai General Hospital - Dang Quang, Tran; Dung, Do Thi Phuong (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 1, 2025)
Linezolid is an important reserve antibiotic to treat drug-resistant Gram-positive bacterial infections. However, this antibiotic can cause adverse events such as thrombocytopenia. Identifying and characterizing linezolid-induced thrombocytopenia and risk factors associated with linezolid-induced thrombocytopenia play a crucial role in improving the efficacy and safety of treatment for patients. Therefore, this study aimed to investigate linezolid-induced thrombocytopenia and to identify potential risk factors affecting linezolid-induced thrombocytopenia in patients using linezolid at Dong Nai General Hospital. A descriptive cross-sectional study on 179 patients using linezolid between January 1, 2022, and December 31, 2022, who met the study conditions. There were 42 patients (23.5%) who experienced thrombocytopenia. Most patients had mild thrombocytopenia (57.1%). The average duration of treatment with linezolid is 8-14 days (57.1%). Age, gender, estimated glomerular filtration rate before using linezolid, treatment duration, invasive interventions, and intermittent hemodialysis had statistically significant differences between the group of patients with thrombocytopenia and those without thrombocytopenia (p < 0.05). Multivariable logistic regression tests showed that the risk of thrombocytopenia events increased in patients with eGFR < 30 ml/min/1.73 m 2 (p < 0.001) and in the group of patients treated with linezolid for 8-14 days (p = 0.001) and ≥ 15 days (p < 0.001). It is necessary to closely monitor platelet counts in special patients with impaired renal function (CrCl < 30 ml/min/1.73 m 2 ) and patients using linezolid for a long duration (8 days or more).